Teacher's Efforts to Improve Reading Interest in 5-6 Years Old Children during COVID-19 Pandemic - Ayu Wulandari; M. Syukri; Andini Linarsih (Universitas Tanjungpura, 2022)
The research on teachers' efforts to increase interest in reading children aged 5-6 years during COVID-19 pandemic at Integrated Early Childhood Education (PAUD) of Kartini was motivated by the exposure of UNESCO data which stated that Indonesia ranked second from the bottom in terms of world literacy, meaning that reading interest in Indonesia is very low. According to UNESCO data, the reading interest of the Indonesian people is very concerning, only 0.001%. This study aims to determine the efforts of teachers to increase interest in reading for children aged 5-6 years during the COVID-19 pandemic at the Integrated PAUD of Kartini in Pontianak. The research method used was descriptive qualitative research methods with case study research. The study results in an effort by teachers to increase reading interest in children aged 5-6 years during the COVID-19 pandemic at the Kartini Integrated PAUD Pontianak were carried out using various media methods and conducting appropriate learning evaluations to increase children's reading interest.Â Keywords: Reading Interests, Methods, Media, Evaluation, COVID-19 Pandemic